An American spy - Steinhauer, Olen. (New York : St. Martin's Paperbacks, 2013)
When the CIA's Department of Tourism is dismantled by a Chinese intelligence scheme that has caused numerous agent deaths, survivor Milo Weaver is placed at risk by his former boss, Alan Drummond, who uses one of Milo's aliases to exact revenge.
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; Undercover operations -- Fiction; Spy stories; Suspense fiction